Now! - Corderoy, Tracey (Tiger Tales, 2016)
Otto doesn't like to wait. He wants to do things NOW! Even though Dad is on the phone, Otto wants him to read a book NOW! When Otto gets in line for the bouncy castle, he wants his turn NOW! One day, Mom tells Otto that the family is going on vacation -- and, of course, Otto wants to go NOW! Will Otto ever learn to be patient?